Inflammatory and Regenerative Responses of the Epididymis Following Local Anesthesia: An Immunohistochemical Study - Dilnoza, Khasanova; D., Kodirov M. (American Journal of Biomedicine and Pharmacy, 2026)
This experimental study evaluated immunohistochemical changes in epididymal tissue following different methods of local anesthesia using lidocaine and novocaine. A white outbred rat model was used with markers of inflammation (CD45) and regenerative potential (CD56). Intratesticular administration was associated with increased inflammatory activity (↑CD45) and reduced regenerative capacity (↓CD56), with the most pronounced effects observed after novocaine injection. In contrast, conduction anesthesia, particularly with lidocaine, showed lower CD45 expression and relative preservation of CD56-positive cells. A combined approach (lidocaine conduction anesthesia with microdose intratesticular novocaine) reduced inflammation while maintaining regenerative potential. These findings demonstrate that the route of anesthetic administration critically influences the immunomorphological response of epididymal tissue and support the use of less traumatic combined protocols in scrotal interventions.